Krishna
0

Step 1: Isolate either x or y from the linear equation(or low power equation):


EXAMPLE: x + y = 2

                  x= 2 - y or y = 2 - x

Step 2: Substitute x or y values into the second equation and simplify


EXAMPLE: x^2+y^2=12                   (2 - y)^2 + y^2 = 12

                   4 - 4y + y^2 = 12

                   y^2 - 4y - 8 = 0


Step 3: Solve the quadratic equation by using the formula or any other method.


EXAMPLE: y^2 - 4y - 8 = 0

                    (x – 4)(x + 2) = 0

                            x = 4, x = –2

Step 4; Substitute these values of  x into the second equation to find y